Becoming men of some consequence : youth and military service in the Revolutionary War - Ruddiman, John A., 1978- (Jeffersonian America., 2014)
"This book examines young Revolutionary War soldiers' and officers' changing motivations and expectations in relation to their enlistments, experiences in the army, choices about quitting long-term military service, and their attempts to rejoin civilian life after the war"--Provided by publisher.